Bayesian gravity model for digitalization on bilateral trade integration in Asia - S. P. Jayasooriya (Asian Development Bank Institute (ADBI), 2021)
The impact of globalization in terms of bilateral trade is a renowned theoretical underpinning in the literature. Nevertheless, testing a trade integration model of bilateral trade is not sufficiently well estimated with the Bayesian approach to provide pragmatic evidence of trade integration from the digitalization in Asia. Moreover, in identifying the factors determining trade integration, testing for digitization using the Bayesian gravity equation is vital. After performing a series of simulation experiments, a relationship between import volume and simulated trade determinants was predicted for the digitalized trade model. The results of the estimated coefficients on GDP in the country of origin and GDP of the country of destination are positively significant predictors of the import growth. The distance between the countries has a negatively significant estimation that implies barriers in trade. The model predicts trade integration, especially towards the trade digitalization in Asia. The Bayesian approach of the gravity model gives robust estimates for determining the impact factor for the importation of trading countries, including the fact that the elasticities of total trade inflow with respect to distance, population, and area of the country of destination and the exchange rate of the country of origin are negative while the proxies of digitization are positively significant. Further, economic size, area, and exchange rate of the destination, and population and area of the country of origin are positively predicted by the model. The estimated parameters are directly the elasticities, in which increases in GDP in a reporter country is consistent with the higher import volumes. Further, evidence of the gravity equation is used for understanding trade potential, and after some integrations, the estimation is applied for the real trade. The measures of bilateral trade resistance or costs associated with the trade flow of the digitization has influenced the expanding of the digital indicators in the model in the Asian economies. Finally, digitalization of trade integration can be implemented across Asia with evidence and robust estimates of the gravity model, including robustness checking. The Bayesian experiment for the estimation of the impacts of the trade integration in Asia predicts an increase of GDP, digitalization proxies, population, exchange rate, and area of the destination as predominant predictors in the Bayesian gravity model. Thus, the results revealed that digitalization has affected the plausible trade agreements for trade integration in Asia.
Keywords: F11; F14; F15; F62; 330; Bayesian gravity model; digitization; import growth; trade integration